TINDAK TUTUR EKSPRESIF DALAM PEMBELAJARAN BAHASA INDONESIA - Haslinda Haslinda (Jurnal Panrita, 2022)
Expressive Speech Acts (Case Study of Class XI Students of Public High School 2 Soppeng), Problems in communication and language skills. This study aims to describe the form of expressive speech acts in students of class XI MIPA 2. This research is a descriptive study with a qualitative approach. The subject of this research is the speech of students of class XI MIPA 2 Public High School 2 Soppeng. The data is obtained through screenshot documentation and then recorded and reviewed. The results of this study conclude that the forms of expressive speech acts are (1) speech acts of congratulating 6 times (17.64%), (2) speech acts of praising as much as 8 times (23.52%), (3) speech acts of gratitude 5 times (14.70%), (4) condolences 3 times (8.82%), (5) blaming speech acts 6 times (17.64%), and (6) apologizing as much as 6 times (17.64%).